Tindakbalas imuniti mukosa dan humoral kambing terhadap semburan intranasal pasteurella multocida B:2 yang dinyahaktif - Siti Tafsil Raudah Sh Abdul Kadir (Fakulti Sains dan Teknologi, 2011)
Pasteurella multocida B:2 is a gram negative bacteria belonging to the family of Pasteurellacea. The infection of P.multocida B:2 known as Haemorrhagic septicaemia or Hawar Berdarah (HB) disease could causes acute pneumonia and acute death to the infected animals especially to the cattle and water buffaloes.